2002
DOI: 10.1182/blood.v99.1.207
|View full text |Cite
|
Sign up to set email alerts
|

Activation of CD8 T cells induces expression of CD4, which functions as a chemotactic receptor

Abstract: IntroductionThe CD4 protein has many different functions in the development and activity of a T cell. CD4 has an important role in T-helper (Th)-cell development and response to antigen in the context of major histocompatibility complex class II (MHC II). It also serves as an adhesion molecule and a chemotactic receptor, and it has a role in cellular activation. CD4, a 58-kd transmembrane glycoprotein, is a member of the immunoglobulin family of receptors. 1 The extracellular 370-amino acid portion of CD4 is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
64
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 33 publications
2
64
0
Order By: Relevance
“…Recent studies have suggested that IL-16 may signal through an alternative receptor in cells from the monocytoid lineage, as CD4 null epidermal dendritic cells and monocytes obtained from CD4 null mice are responsive to IL-16 (9,10). In T cells, however, the data indicate a requirement of CD4 expression for induction of a cellular response to IL-16 stimulation (3,11,12). Although CD4 is required, it has not been established whether all CD4 ϩ T cells are responsive to IL-16 stimulation or whether there is a preferential subset effect.…”
mentioning
confidence: 61%
“…Recent studies have suggested that IL-16 may signal through an alternative receptor in cells from the monocytoid lineage, as CD4 null epidermal dendritic cells and monocytes obtained from CD4 null mice are responsive to IL-16 (9,10). In T cells, however, the data indicate a requirement of CD4 expression for induction of a cellular response to IL-16 stimulation (3,11,12). Although CD4 is required, it has not been established whether all CD4 ϩ T cells are responsive to IL-16 stimulation or whether there is a preferential subset effect.…”
mentioning
confidence: 61%
“…We have previously determined that CD4 can function as a chemotactic receptor on activated human CD8 ϩ T cells, allowing them to migrate in response to IL-16 (16). Furthermore, we have recently determined that CD4 can directly influence human CD8 T cell function in vitro (9).…”
mentioning
confidence: 99%
“…The upregulation of CD4 on CD8 + T cells can be induced by strong activation and has been shown to be involved in interacting with HLA-class II, IL-16-induced chemotaxis and enhanced effector functions. 25,33 Functional studies with one of the prominent brain-derived CD4 dim CD8 + TCCs revealed CD8-dependent recognition of a LTAg epitope with high affinity, Tc1 profile and cytotoxic potential.…”
Section: Discussionmentioning
confidence: 99%
“…Since blocking of the CD4 receptor in the CD4 dim CD8 + TCC did not alter the response to the peptide, and since CD4 is known to serve as a receptor for soluble IL-16 33 , we expect that co-expression of CD4 is primarily serving a role in chemotactic recruitment of CD4 dim CD8 + T cells to the site of inflammation in the cerebellum. 37,38 Our data provide novel information on host-pathogen interactions during CNS infection with JCV and illustrate alongside with the recently described antibody "recognition holes" for JCV variants in natalizumab-associated PML 39 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation